Interpreting PPE Statements on Pesticide Labels - Olaf N. Nesheim (EDIS)
Many Personal Protective Equipment (PPE) statements on pesticide labels have been changed as a result of the Worker Protection Standard for Agricultural Pesticides (WPS). PPE statements on products that are labeled for use on farms, forests, nurseries and greenhouses, in particular, have been revised. These revised statements are more precise on the type of PPE that must be worn by pesticide handlers (mixers, loaders,and applicators). The terminology used to describe the required PPE is now more consistent from label to label. The chart in this document lists label statements used to describe the PPE required for use by mixers, loaders, and applicators. The accompanying column of acceptable PPE describes the options the pesticide handler has when the label statement lists a specific item of PPE. This document is PI-16, Horticultural Sciences Department, UF/IFAS, Florida Cooperative Extenstion Service. September 2003.